Pengaruh Progressive Muscle Relaxation (PMR) Terhadap Tingkat Stres Pada Ibu-Ibu PKK Usia Dewasa Tengah Di Dusun Ngegot, Selokaton, Gondangrejo, Karanganyar - Lis Sarwi Hastuti (Jurnal Keterapian Fisik, 2019)
Background: Middle adulthood (40-59 years) is a transition period from early adulthood to late adulthood (elderly) which is marked by several changes, including physical / biological, mental, cognitive changes. This change has the potential to cause stress. This study aims to determine whether there is an effect of the provision of Progressive Muscle Relaxation / Progressive Muscle Relaxation on Stress Levels in middle-aged adult mothers in Ngegot villages, Selokaton, Gondangrejo, Karanganyar. The sampling technique in this study is to use total sampling. The number of samples in this study amounted to 26 respondents. This research is a type of pre-experimental research with one group pre-test and post-test design methods. Methods: The data analysis method used was a paired sample t-test statistical test technique with the help of SPSS 17.0. Data normality test used is by Shapiro-Wilk. Results: From the results of the analysis of the research data the normality of the data obtained the significance value with Shapiro-Wilk in the pre-test of 0.388 (p> 0.005) and post test of 0.073 (p> 0.005). Significance Value of the Effect of Progressive Muscle Relaxation Against Stress in middle adult mothers in Ngegot, Selokaton, Gondangrejo, Karanganyar villages with paired sample t-test analysis p = 0.001.Conclusion: The results of this study indicate that there is an effect of Progressive Muscle Relaxation on Stress Levels in middle adult mothers in Ngegot, Selokaton, Gondangrejo, Karanganyar hamlets.